Adaptive filter and pulse-shaping for interference cancellation of differential quadrature phase-shift keying modulation - Rahmad Hidayat; Farhan Adani (Indonesian Journal of Engineering Research, 2021)
Differential quadrature phase-shift keying (DQPSK) modulation methods and variations are commonly used in wireless communication, including high-speed optical fiber, Bluetooth, and satellite communication. DQPSK cannot be isolated from possible interference with its present application. The interference cancellation process has been observed and analyzed using a device model built in this study. The core components of the supporting block for this device model have raised cosine filters for pulse shaping and adaptive filters. The presence of these core components has resulted in a dramatic improvement in device efficiency, according to robust Simulink data. The best bit error rate (BER) of 5.7e-03 provides evidence of this.